Pengembangan Bahan Ajar Berbasis Lingkungan Sekitar Pada Siswa Kelas IV Sekolah Dasar - Hasnawati Hasnawati (Pedagogik Journal of Islamic Elementary School, 2020)
Research aims to find out how avalid and effective environment-based teaching material is designed. This research is a research method of research&Development (R&D). To develop the product, this research follows the design of 4-D developmentmodel that includes four phases: Define, Design, Develop, Disseminate. The trial subjects were 18 students in class IV SDIT Al-Bashirah city Palopo. The results of the validity of the design teaching book are obtained by the value 4.18 with valid categories. The effectiveness of teaching materials is analyzed based onthe results of student study test and studen response after testing conducted. Theresults of  the test analysis obtained anaverage of 79.16 good categories with a percentage of 89%. While the results of the student responses poll analysis obtained 81.29% of students respond positively to teaching materials. The analysis was concluded that the neighbourhood-based teaching book wasincluded in the criteria for the validity and effectiveness of the teaching materials.